Potential pre-industrial-like new particle formation induced by pure biogenic organic vapors in Finnish peatland - Huang, Wei; Junninen, Heikki; Garmash, Olga; Lehtipalo, Katrianne; Stolzenburg, Dominik; Lampilahti, Janne L. P.; Ezhova, Ekaterina; Schallhart, Simon; Rantala, Pekka; Aliaga, Diego; Ahonen, Lauri; Sulo, Juha; et al. (American Association for the Advancement of Science, 2024)
Pure biogenic new particle formation (NPF) induced by highly oxygenated organic molecules (HOMs) could be an important mechanism for pre-industrial aerosol formation. However, it has not been unambiguously confirmed in the ambient due to the scarcity of truly pristine continental locations in the present-day atmosphere or the lack of chemical characterization of NPF precursors. Here, we report ambient observations of pure biogenic HOM-driven NPF over a peatland in southern Finland. Meteorological decoupling processes formed an “air pocket” (i.e., a very shallow surface layer) at night and favored NPF initiated entirely by biogenic HOM from this peatland, whose atmospheric environment closely resembles that of the pre-industrial era. Our study sheds light on pre-industrial aerosol formation, which represents the baseline for estimating the impact of present and future aerosol on climate, as well as on future NPF, the features of which may revert toward pre-industrial–like conditions due to air pollution mitigation.
Keywords: new particle formation; peatlands; pure biogenic organic vapors